Aperfeiçoamento da distribuição de hidrogênio em reatores do tipo coluna de lama borbulhante aplicado ao hidrocraqueamento das frações pesadas do petróleo através da fluidodinâmica computacional - Costa, Juliana Guerhart da (2014)
The gas-liquid-solid flow reactors in slurry bubbling column are usually encountered in industry. Despite the fact of being a simple machine, a large difficulty is found in their study of complex fluid dynamics, due the flow patterns, caused by the liquid recirculation zones and the ascendancy the bubbles. The objective this research is to improve the process of hydroconversion of heavy petroleum fractions, improving the distribution of the injected hydrogen, which will be done on the sides of the reactor, in order to reduce the hydrogen-poor area, using Computational Fluid Dynamics (CFD). The application of Computational Fluid Dynamics in industrial operations has been increasing significantly for assisting in the design of new equipment, as well as the optimization of existing ones, which is the case in this research. For this, were studied the fluid dynamics of the reactor with no entries and with gas injection by side, to compare results. The reactor has dimensions 4m x 0.3m (height (H) x diameter (D)). The final model tested, with lateral inlets, satisfactorily predicted the goal of improving the distribution of gas in regions where it was missing.